(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
This study explores the association between spiritual accounting practices and corporate financial reporting quality with a focus on stewardship, accountability, transparency and honesty, ethical decision-making and CSR integration with audit quality. Drawing from stakeholder theory and stewardship theory, the study argues that integrating spiritual values into accounting practices enhances the credibility and reliability of financial reports. Using a cross-sectional survey of accounting professionals and financial managers of firms listed on the NGX, data were collected and analysed through descriptive and inferential statistics to test the hypothesised association. The findings reveal a strong and positive association between stewardship of spiritual accounting and the reliability of financial reports of firms listed on the NGX in Nigeria; a strong and positive association between accountability of spiritual accounting and the reliability of financial reports of firms listed on the NGX in Nigeria; a strong and positive association between transparency and honesty of spiritual accounting and the reliability of financial reports of firms listed on the NGX in Nigeria; a strong and positive association between ethical decision-making of spiritual accounting and the reliability of financial reports of firms listed on the NGX in Nigeria; a strong and positive association between corporate social responsibility of spiritual accounting and the reliability of financial reports of firms listed on the NGX in Nigeria and a strong and positive association between audit quality and the reliability of financial reports of firms listed on the NGX in Nigeria. The study contributes to the growing body of literature on spirituality in business and financial ethics by demonstrating the practical role of spiritual accounting in enhancing reporting quality. It also provides useful implications for policymakers, who should encourage the integration of spiritual and ethical principles into financial reporting guidelines and professional training. Finally, the study highlights the need for future research to develop standardized measurement instruments for spiritual accounting and to extend the investigation across industries.